Priapism following a juvenile Russell's viper bite: An unusual case report. - Subramanian Senthilkumaran; Harry F Williams; Ketan Patel; Steven A Trim; Ponniah Thirumalaikolundusubramanian; Sakthivel Vaiyapuri (PLoS Neglected Tropical Diseases)
Following a bite from a juvenile Russell's viper (Daboia russelii), a priapism (painful erection) developed rapidly in a 16-year-old male and only subsided after administration of antivenom 3 hours later. Potential mechanisms for this snakebite-induced priapism are unclear but likely due to venom toxins causing nitric oxide (NO) release and subsequent vasodilation of endothelium in the corpus cavernosum, although the possible involvement of other mechanisms cannot be ruled out. We strongly believe that this unusual case report may lead to further scientific research in order to improve the clinical understanding of the pathophysiology of envenomation due to Russell's viper bites. Although it is too early to speculate, further research may also discover the possibilities of developing venom-based candidate molecules to treat sexual dysfunction in males and females.